مساهمة إدارة المعرفة في إستدامة المؤسسات الإقتصادية - يمينة طواهرية; يمينة باهي; زينب احموده; سهام بوسكاية (university of eloued جامعة الوادي, 2024)
": تهدف هذه الدراسة إلى معرفة مدى مساهمة إدارة المعرفة في إستدامة مؤسسة إتصالات الجزائر بولاية الوادي و ذلك من خلال محاولة الإجابة على الإشكالية الرئيسية التالية: كيف تساهم إدارة المعرفة في إستدامة مؤسسة إتصالات الجزائر بولاية الوادي ؟ وقد إعتمدت الدراسة على المقابلة و الإستبانة كأداة لجمع البيانات،حيث تم توزيع (59) إستمارة على عينة الدراسة، كما تم تحليل البيانات بإستخدام يرنامج spss.v25 ، وقد توصلت الدراسة إلى مجموعة من النتائج أهمها : أن مؤسسة إتصالات الجزائر بولاية الوادي تتصف بالمرونة و قدرتها على البقاء، والإستمرارية، والثبات و تحقيق ديمومة نشاطها الإقتصادي، وكذا توصلت الدراسة إلى وجود إرتباط معنوي و أثر ذو دلالة إحصائية مابين إدارة المعرفة و إستدامة المؤسسة ،ولكن في نفس الوقت فإن تطبيق أبعاد إدارة المعرفة (توليد،تخزين،نشر،تطبيق ) في مؤسسة إتصالات الجزائر بولاية الوادي ، هو متوسط إلى جيد جدا على جميع الأبعاد، الأمر الذي يحتم ضرورة تبني مفاهيم إدارة المعرفة، و العمل على وضع أسلوب لإدارة المعرفة ،يتميز بقابلية للتطوير ليتماشى مع طبيعة نشاط المؤسسة بهدف تحقيق إستدامتها. " "This study aims to determine the extent to which knowledge management contributes to the sustainability of the Algeria Telecom Corporation in the Province of EL Oued, by trying to answer the following main problem: How does knowledge management contribute to the sustainability of the Algeria Telecom Corporation in the Province of EL Oued? The study relied on the interview and questionnaire, as a tool for collecting data, where (59) questionnaires were distributed to the study sample, and the data was analyzed using the SPSS.V25 program.The study reached a set of results, the most important of which are: that the Algeria Telecom Corporation in the state of EL Oued is characterized by flexibility, And its ability to survive, continue, and achieve stability and sustainability of its economic activity. The study also found that there is a moral relationship and a statistically significant effect between knowledge management and the sustainability of institutions, but at the same time, the application of the dimensions of knowledge management (generation, storage, dissemination, application) At the Algeria Telecom Corporation in the state of EL Oued, it is average to very good in all dimensions, which necessitates the need to adopt knowledge management concepts, and work to develop a method of knowledge management that is characterized by the possibility of development to be in line with the nature of the organization’s activity in order to achieve its sustainability. "
Keywords: إدارة المعرفة، إستدامة المؤسسات، توليد المعرفة ، تطبيق المعرفة ، SPSS; knowledge management; instutional sustainability; knowledge generation; application of knowledge; SPSS